QSPR Evidences for Topological Indices to Mimic Lipophilicity of Thia and Aza-Crown Ethers - Bhagwat, V.W.; Khadikar, P.V.; Tiwari, Akshay; Solanki, Aruna; Choubey, Ajit; Kamal, Neel; Manana, Prerna; Lowlekar, Vaibhav (Asian Journal of Chemistry, 2010)
QSPR study on a large set of thia and aza crown ethers has been carried out for the modelling of lipophilicity, using topological indces. The stepwise multilinear regression analysis of the data has indicated that an excellent model is obtained when these topological indices are combined with some structural indcators. The obtained models are critically discussed and examined by various types of cross validation parameters.